Edukasi Pengolahan Makanan Sehat di RA Perwanida 15 Menuju SDGs Desa Sempolan Peduli Kesehatan - Chamelia Putri; Prima Ratna Sari; Sela Rachmawati; Kuswati Kuswati (JURPIKAT, 2026)
Preliminary study with the Head of the RA Perwanida 15 indicate a highly concerning issue: the absence of healthy food options for the children. In contrast, the village have strong potential as a source of nutritious food for children. The primary issue in the community’s limited knowledge and lack of initiative regarding the provision of healthy meals for children. This community service program implemented as an effective strategy to promote healthy and nutritious food through structured educational activities. The program targeted 37 mothers of students enrolled at school. The implementation team employed surveys, lectures, question-and-answer sessions, training demonstrations, and evaluation methods to deliver the educational content. The program was carried out through several stages, including needs analysis, coordination, educational delivery, and evaluation. The results indicate an improvement in the mothers’ knowledge of healthy and nutritious food after participating in the educational sessions and studying the module prepared by the team.